The phenomenon of signed music in Deaf culture - Radić Šestić, Marina; Šešum, Mia; Ljubica Isakovic, Ljubica (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Music in the Deaf community is a socio-cultural phenomenon that depicts a specific identity and way of experiencing the world, which is just as diverse, rich and meaningful as that of members of any other culture. Objective. The aim of this paper was to point out the historical and socio-cultural frameworks, complexity, richness, specific elements, types and forms of musical expression of members of the Deaf community. Methods. The applied methods included comparative analysis, evaluation, and deduction and induction system. Results. Due to limitations or a lack of auditive component, the members of Deaf culture use different communication tools, such as speech, pantomime, facial expressions and sign language. Signed music, as a phenomenon, is the artistic form which does not have long history. However, since the nineties of the past century and with technological development, it has been gaining greater interest and acknowledgement within the Deaf community and among the hearing audience. Signed music uses specific visuo-spatial-kinaesthetic and auditive elements in expression, such as rhythm, dynamism, rhyme, expressiveness, iconicity, intensity of the musical perception and the combination of the role of the performer. Conclusion. Signed music as a phenomenon is an art form that incorporates sign poetic characteristics (lyrical contents), visual musical elements and dance.
Keywords: phenomenon; signed music; Deaf culture